2019
DOI: 10.1002/eat.23032
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating among Australian adolescents: Prevalence, functioning, and help received

Abstract: Objective To estimate the prevalence of disordered eating (DE) among Australian adolescents and examine associations with clinical mental health problems, problems with functioning, and help received. Method We analyzed data from the Young Minds Matter survey (n = 2,298, 13–17 years). We derived an index of DE severity with four levels: (1) no DE; (2) subclinical DE; (3) suspected eating disorder; and (4) lifetime eating disorder diagnosis. Results In 2013–2014, 31.6% (95%CI 35.5–39.9) of Australian adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 51 publications
4
33
0
4
Order By: Relevance
“…The data from some other studies had higher prevalence rates, for example, 1-month prevalence of 2.3% in a Madrid primary care study and no cases of anorexia, which was congruent with our study [37]. Another study showed that people with eating disorders sought help using schoolbased, primary care or specialist services in 40% of cases [47]. These data highlight the importance of screening for eating disorders in primary care settings.…”
Section: Table 2 Prevalence (%) Of Comorbidity Between Diagnostic Groupssupporting
confidence: 90%
“…The data from some other studies had higher prevalence rates, for example, 1-month prevalence of 2.3% in a Madrid primary care study and no cases of anorexia, which was congruent with our study [37]. Another study showed that people with eating disorders sought help using schoolbased, primary care or specialist services in 40% of cases [47]. These data highlight the importance of screening for eating disorders in primary care settings.…”
Section: Table 2 Prevalence (%) Of Comorbidity Between Diagnostic Groupssupporting
confidence: 90%
“…In much lower frequency it appears for the rst time in women in their late youth or in middle age [45,46]. A study regarding the period 2013-2014 reported that 31.6% of Australian adolescents experienced disordered eating [47]. A meta-analysis of 41 studies showed increase in prevalence of eating disorders (3.7% vs. 1.8%) [48].…”
Section: Discussionmentioning
confidence: 99%
“…At a much lower frequency, it appears for the rst time in women in their late youth or in middle age [45,46]. A study regarding the period 2013-2014 reported that 31.6% of Australian adolescents experienced disordered eating [47]. A meta-analysis of 41 studies showed an increase in the prevalence of eating disorders (3.7% vs. 1.8%) [48].…”
Section: Discussionmentioning
confidence: 99%